2021
DOI: 10.34133/2021/5130420
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Molybdenum-Based Materials for Lithium-Sulfur Batteries

Abstract: Lithium-sulfur (Li-S) batteries as power supply systems possessing a theoretical energy density of as high as 2600 Wh kg−1 are considered promising alternatives toward the currently used lithium-ion batteries (LIBs). However, the insulation characteristic and huge volume change of sulfur, the generation of dissolvable lithium polysulfides (LiPSs) during charge/discharge, and the uncontrollable dendrite formation of Li metal anodes render Li-S batteries serious cycling issues with rapid capacity decay. To addre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 137 publications
0
30
0
Order By: Relevance
“…Owing to their superior theoretical capacity of 1675 mAh g −1 and energy density of 2600 Wh k g −1 , LSBs hold the potential to fulfill the demand of 500 kilometers per charge for practical applications in electric vehicles, which corresponds to an energy density of 500-600 Wh kg −1 . [166][167][168] Zhang et al modified the separator with amorphous MIL-88 nanoprisms which were transformed from their crystal counterparts via a ligand exchange method (Figure 14a). [169] It was found that 2-MeIM can substitute amino terephthalate and the subsequent hydroxylation promoted the release of organic ligands, resulting in the amorphization of MIL-88 crystals.…”
Section: Applicationsmentioning
confidence: 99%
“…Owing to their superior theoretical capacity of 1675 mAh g −1 and energy density of 2600 Wh k g −1 , LSBs hold the potential to fulfill the demand of 500 kilometers per charge for practical applications in electric vehicles, which corresponds to an energy density of 500-600 Wh kg −1 . [166][167][168] Zhang et al modified the separator with amorphous MIL-88 nanoprisms which were transformed from their crystal counterparts via a ligand exchange method (Figure 14a). [169] It was found that 2-MeIM can substitute amino terephthalate and the subsequent hydroxylation promoted the release of organic ligands, resulting in the amorphization of MIL-88 crystals.…”
Section: Applicationsmentioning
confidence: 99%
“…Capping agent-based synthetic methods are widely used in the field of catalysis, which has powered the development of artificial fertilizers, solar cells, high-strength polymers, electrocatalysis, and alkali metal–sulfur/oxygen batteries. 1–9 In a colloidal synthesis process, 10,11 long-chain capping agents inhibit the aggregation and overgrowth of catalyst materials at the nanoscale, and modulate the structural characteristics of crystal facets via precise interfacial tailoring. 10 Specifically, the functionalized surface of catalysts plays a crucial role in lithium–sulfur (Li–S) batteries during redox reactions of soluble polysulfides on the interface, 12–14 where better performance depends on utilization and anchoring of migratory polysulfides on the cathode.…”
Section: Introductionmentioning
confidence: 99%
“…The energy crisis and environmental pollution caused by the burning of fossil fuels urgently require researchers to develop green and efficient energy storage systems. [1] Among various candidates, lithium-ion batteries (LIBs) have been well commercialized and applied as the dominating charge storage devices in the market owing to their relatively higher energy density in Therefore, it is reasonably speculated that combining nanostructure design and heterogeneous hybridization takes a good chance to make full use of both conversion-type and intercalation-based anode materials. Nevertheless, it lacks suitable synthetic strategy due to the poor thermal/chemical stability of MXene and the electrostatic repulsive force between MXene and TMOs originated from the similar negatively charged surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…The energy crisis and environmental pollution caused by the burning of fossil fuels urgently require researchers to develop green and efficient energy storage systems. [ 1 ] Among various candidates, lithium‐ion batteries (LIBs) have been well commercialized and applied as the dominating charge storage devices in the market owing to their relatively higher energy density in comparison with aqueous‐based secondary batteries. [ 2,3 ] However, the ever‐increasing demands of energy storage and supply systems are driven by the rapid development of portable/wearable electronics are severely limited by the low theoretical capacity of the commonly used graphite anode.…”
Section: Introductionmentioning
confidence: 99%